THE LANGUAGE SITUATION AND LANGUAGE POLICY IN MODERN UKRAINE AND POLAND: A COMPARATIVE ASPECT - Barchuk-Halyk, Maryana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
This article offers a general overview of language dynamics and policies in Ukraine and Poland. It examines the impact of political changes stemming from the Russian Federation's aggression and full-scale war on the linguistic landscape. Furthermore, the article delves into the security aspects of language policies within the broader contexts of human and national security challenges.